(untitled) (Prostor, 2022)
This study aims to demonstrate the acculturation of Seljuk architecture and construction techniques by tracing the development of peripheral walls in Seljuk wooden hypostyle mosques built in 13th and 14th centuries. To track the exchange of construction knowledge two Seljuk mosques (the Hanönü Mosque in Kastamonu and the Ahi Elvan Mosque in Ankara) are selected for comparison in this study. The main difference between the two mosques is their structural systems: one has a wooden peripheral wall and wooden skeleton system, while the other has a masonry peripheral wall and wooden pillars. In this study, a comparison of the structural systems and performances of these examples of wooden mosques exhibiting different wall systems was made together with structural analyses under basic loads. A series of structural analyses provides significant data about the structural behaviour of these types of structures, indicating acculturation of elements from Asia and Byzantium within Seljuk architecture and construction techniques.